2014
DOI: 10.2147/ov.s56322
|View full text |Cite
|
Sign up to set email alerts
|

Applications of coxsackievirus A21 in oncology

Abstract: The clinical management of cancer continues to be dominated by macroscopic surgical resection, radiotherapy, and cytotoxic drugs. The major challenge facing oncology is to achieve more selective, less toxic and effective methods of targeting disseminated tumors, a challenge oncolytic virotherapy may be well-placed to meet. Characterization of coxsackievirus A21 (CVA21) receptor-based mechanism of virus internalization and lysis in the last decade has suggested promise for CVA21 as a virotherapy against maligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 51 publications
0
69
0
Order By: Relevance
“…Upregulation of ICAM-1 in melanoma is well studied, and it has been considered a relevant marker in disease prognosis [160]. It has been suggested that ICAM-1 is responsible for metastasis generation, as it facilitates cell-cell interactions between malignant melanocytes and circulating lymphocytes [95]. Upregulation of ICAM-1 in melanoma could be a potential target for CVA21 therapy as has been reported [158].…”
Section: Preclinical Studies With Cva21mentioning
confidence: 93%
“…Upregulation of ICAM-1 in melanoma is well studied, and it has been considered a relevant marker in disease prognosis [160]. It has been suggested that ICAM-1 is responsible for metastasis generation, as it facilitates cell-cell interactions between malignant melanocytes and circulating lymphocytes [95]. Upregulation of ICAM-1 in melanoma could be a potential target for CVA21 therapy as has been reported [158].…”
Section: Preclinical Studies With Cva21mentioning
confidence: 93%
“…Coxsackievirus A21 (CVA21) is a promising OV that depends on highly expressed receptor molecules on the surface of tumor cells, intercellular adhesion molecule-1 (ICAM-1, also named CD54), and decay-accelerating factor to preferentially enter, replicate in, and kill tumor cells. CVA21 exhibited antitumor efficacy in multiple cancers, including melanoma, prostate cancer, and multiple myeloma [30]. A CVA21-based OV (CAVATAK ® ) has been assessed in clinical trials for the treatment of malignant melanoma, bladder cancer [58], and uveal melanoma with liver metastases [59].…”
Section: Wild-type Ovs In Oncolytic Virotherapymentioning
confidence: 99%
“…Most oncolytic viruses exert anti-tumor activity by penetrating the tumor cells, establishing a lytic cycle and ultimately causing the activation of cell death pathways. While some OVs have the natural capacity to infect specific tumors through receptor-mediated internalization, 14,[16][17][18] most OVs have been engineered to enhance their tumor selectivity and to reduce virulence in normal cells. 12,13,19,20 Even though natural receptors responsible for oncolytic viral entry are expressed on non-malignant cells thereby allowing a successful infection, [21][22][23] OVs often require a defect in innate immunity to successfully infect and propagate, which is only present in tumor cells but not in healthy cells.…”
Section: Mechanisms Of Oncolysismentioning
confidence: 99%